2002
DOI: 10.1016/s0377-8401(02)00182-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of urea, isolated soybean protein and blood meal on growing steers fed a corn-based diet

Abstract: A short term feeding trial was conducted to assess effects of nitrogen (N) supplementation on growing cattle and the ability of the Cornell Net Carbohydrate and Protein System (CNCPS) to predict responses. Four corn-based diets were used: (1) a 30% ruminal N-deficient control diet; (2) a urea supplemented diet; (3) a urea+isolated soy protein (ISP) diet; and (4) a urea+ISP+blood meal (BM) diet. Four Holstein steers (average initial body weight of 251 kg) were randomly assigned in a 4 × 4 Latin Square treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
4
9
0
1
Order By: Relevance
“…This might be attributed to the high nutritional characteristics of soy waste, including ME and CP contents. Knaus et al (2002) reported that N absorption and N retention increased, when soy protein-based diets were fed to steers. Kim et al (2012) also reported that dietary soybean curd residue could improve the growth rate of cattle.…”
Section: Resultsmentioning
confidence: 99%
“…This might be attributed to the high nutritional characteristics of soy waste, including ME and CP contents. Knaus et al (2002) reported that N absorption and N retention increased, when soy protein-based diets were fed to steers. Kim et al (2012) also reported that dietary soybean curd residue could improve the growth rate of cattle.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Guerino et al (1991) and Ragland-Gray et al (1997) found higher plasma insulin after the infusion of casein into the abomasum in steers. But, Knaus et al (2002) observed that plasma glucose and NEFA in growing cattle did not increase when the protein in the diet increased. On the other hand, when decreasing energy sources provided by pineapple waste silage and increasing energy provided by concentrate with increasing in plasma insulin concentration.…”
Section: Discussionmentioning
confidence: 96%
“…The DM, OM, NDF and acid detergent fiber (ADF) digestibility in male Thai swamp buffalo calves ) and Thai-indigenous heifers ) and the DM and OM digestibility in yearling heifers were not altered by dietary CP levels, though a significant increase in the NDF and ADF digestibility was observed with increased dietary CP by Chumpawadee et al (2009). Knaus et al (2002) increased the CP level from 7.9 to 15.3 % in the diet of growing steers and reported an increase in NDF digestibility from 39.8 to 48.0 %. Mehra et al (2001) reported a non-significant difference in the NDF digestion with increasing levels of energy and protein in experimental diets.…”
Section: Effect Of Dietary Energy and Protein Concentration On Nutriementioning
confidence: 95%